Glycemic Control in Young Men Aged 18–30 Years with Type 1 Diabetes: The Role of Lifestyle and Physical Activity - Dyczek, Paweł; Staniszewska, Wiktoria; Pączek, Adrian; Kowalczyk, Aleksandra; Hofman, Julia (Quality in Sport, 2026)
Introduction: Type 1 diabetes mellitus (T1DM) is a chronic metabolic disease requiring continuous glycemic monitoring and intensive insulin therapy [1]. Early adulthood is a critical period characterized by lifestyle changes that may negatively affect metabolic control, particularly among young men [2,3,17]. Aim: The aim of this study was to analyze factors influencing glycemic control in young men aged 18–30 years with T1DM, with particular emphasis on physical activity and lifestyle behaviors [4,11,18]. Materials and Methods: A narrative review of scientific literature was conducted, including interventional (RCT) and observational studies assessing physical activity and glycemic control in young men with T1DM [5–10,12–16,18–24,30]. Results: Structured physical activity was associated with improvements in HbA1c, time-in-range (TIR), and glycemic variability. Aerobic exercise decreased HbA1c by −0.4% to −0.7% (p < 0.001; 95% CI −0.82 to −0.28), resistance training increased TIR by 6–10% (p = 0.01–0.03), and combined aerobic/resistance training provided the greatest benefits (HbA1c −0.55%; TIR +11–13%; p < 0.001). Observational studies confirmed inverse correlations between overall activity and HbA1c (r = −0.32 to −0.45; p < 0.01) [6,9,12,15,16,19–23,26,27,29]. Conclusions: Structured exercise, particularly combined aerobic and resistance training, exerts clinically meaningful effects on glycemic control in young men with T1DM. Individualized physical activity prescriptions should be integrated into diabetes management [1,4,7–30].